2009
DOI: 10.1074/jbc.m109.062745
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Protein S12 and Aminoglycoside Antibiotics Modulate A-site mRNA Cleavage and Transfer-Messenger RNA Activity in Escherichia coli

Abstract: Translational pausing in Escherichia coli can lead to mRNA cleavage within the ribosomal A-site. A-site mRNA cleavage is thought to facilitate transfer-messenger RNA (tmRNA)⅐SmpB-mediated recycling of stalled ribosome complexes. Here, we demonstrate that the aminoglycosides paromomycin and streptomycin inhibit A-site cleavage of stop codons during inefficient translation termination. Aminoglycosides also induced stop codon read-through, suggesting that these antibiotics alleviate ribosome pausing during termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 55 publications
0
28
0
1
Order By: Relevance
“…Holberger & Hayes examined the effects of streptomycin-resistant rpsL mutations on tmRNA activity (Holberger and Hayes, 2009). The rpsL gene encodes ribosomal protein S12, which is located near the decoding center and has long been known to influence translational fidelity (Kurland et al, 1996).…”
Section: Tmrna•smpb and The Mechanism Of Trans-translationmentioning
confidence: 99%
“…Holberger & Hayes examined the effects of streptomycin-resistant rpsL mutations on tmRNA activity (Holberger and Hayes, 2009). The rpsL gene encodes ribosomal protein S12, which is located near the decoding center and has long been known to influence translational fidelity (Kurland et al, 1996).…”
Section: Tmrna•smpb and The Mechanism Of Trans-translationmentioning
confidence: 99%
“…Alternatively, the S12 protein is known to play an important role in the decoding process and may also influence tmRNA acceptance. S12 mutants can inhibit tmRNA tagging, although their mechanism of action is still unclear (Holberger and Hayes 2009;M Miller and A Buskirk, unpubl.). Experiments to determine the mechanisms by which SmpB activates the decoding machinery will likely yield more insight into transtranslation and perhaps canonical decoding as well.…”
mentioning
confidence: 99%
“…Mutations in the rpsL gene have been reported in streptomycin-resistant Gram-positive bacteria Mycobacterium smegmatis (Pelchovich et al, 2013) and Gram-negative bacteria Campylobacter jejuni (Olkkola et al, 2010). It was reported that an amino acid substitution (K42R, K42N, K42T, K42A, K42C, K42S, K42V, K42Y or P90F, P90Y, P90H, P90N) in the rpsL gene of Escherichia coli resulted in mRNA cleavage within the ribosomal A-site (Holberger and Hayes, 2009). The results of the present study suggest that R86W substitution in the rpsL gene was associated with streptomycin resistance.…”
Section: Group Namementioning
confidence: 98%